Pemanfaatan Limbah Industri Abu Batu Kapur dan Sekam Padi Sebagai Pengganti Sebagian Semen Terhadap Campuran Beton Tepat Mutu - Aldi Setiawan; Nurul Lia Suryani; Sendika Renaldi; Alfita Yusriyah (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
With the rapid development on the island of Madura driven by increasing investments due to the impact of the Suramadu Bridge construction, there has also been a significant increase in the use of concrete. Given the growing demand for concrete, an innovation in utilizing local waste materials is necessary, aiming to influence the compressive strength of the concrete. In addition to utilizing local materials such as coarse aggregates from the Waru District in Pamekasan Regency, one of the waste materials that can be used is limestone powder from the Batumarmar District in Pamekasan Regency and rice husk ash from the Proppo District in Pamekasan Regency as a partial replacement for some concrete constituents. This study is a laboratory research aimed at obtaining a concrete mix formula. For the planned testing, concrete in the form of cylinders with dimensions of 15x30 cm is scheduled to be tested at the ages of 7 and 14 days for each mix variation. The study involves several concrete mix variations, namely, 5%, 10%, 15%, and 20% replacement of cement with limestone powder and rice husk ash. The compressive strength test results for the 14-day concrete age showed a consistent decrease in compressive strength with each addition of rice husk ash and limestone powder beyond the 5% replacement. The maximum compressive strength value was found in the 5% variation, with an average compressive strength of 285.41 kg/cm2 at the 7-day concrete age